Repeat-sequence turnover shifts fundamentally in species with large genomes - Novák, Petr; Guignard, Maïté S; Neumann, Pavel; Kelly, Laura J; Mlinarec, Jelena; Koblížková, Andrea; Dodsworth, Steven; Kovařík, Aleš; Pellicer, Jaume; Wang, Wencai; Macas, Jiří; Leitch, Ilia J; et al. (Nature plants, 2020)
Given the 2,400-fold range of genome sizes (0.06-148.9 Gbp (gigabase pair)) of seed plants (angiosperms and gymnosperms) with a broadly similar gene content (amounting to approximately 0.03 Gbp), the repeat-sequence content of the genome might be expected to increase with genome size, resulting in the largest genomes consisting almost entirely of repetitive sequences. Here we test this prediction, using the same bioinformatic approach for 101 species to ensure consistency in what constitutes a repeat. We reveal a fundamental change in repeat turnover in genomes above around 10 Gbp, such that species with the largest genomes are only about 55% repetitive. Given that genome size influences many plant traits, habits and life strategies, this fundamental shift in repeat dynamics is likely to affect the evolutionary trajectory of species lineages.
Keywords: Flow Cytometry; cykasy; genom rostlinný; Retroelements; Cycadopsida; Genome, Plant; průtoková cytometrie; retroelementy; repetitivní sekvence nukleových kyselin; fylogeneze; Phylogeny; Repetitive Sequences, Nucleic Acid; Magnoliopsida